Numera-Q: An Interactive Mathematics Learning Multimedia Design Integrated with Quranic Values to Improve Slow Learner Students' Numeracy Skills - Sugiman; Riawan Yudi Purwoko; Hermawan (Mimbar Ilmu, 2026)
Numeracy skills are essential competencies that students must possess to solve everyday problems, including those with slow learner characteristics. However, students’ low numeracy skills remain a significant issue, influenced by the lack of interactive and contextual learning media, which in turn reduces their motivation to learn mathematics. This study aims to analyze the needs and develop a validated multimedia learning design to support the improvement of numeracy skills among slow learners. The research employed a research and development approach using the ADDIE model, which includes the stages of analysis, design, and development. The subjects consisted of 38 students categorized as slow learners and 4 tenth-grade teachers. Data were collected through questionnaires, structured interviews, focus group discussions (FGD), and documentation, using needs analysis questionnaires and expert validation sheets as instruments. Data analysis was conducted using reduction techniques, triangulation, and descriptive statistics. The results indicate that the need for interactive multimedia learning integrated with Quranic values falls into a high category. Furthermore, expert validation results of the Numera-Q prototype show that it is categorized as highly valid. Therefore, it can be concluded that the Numera-Q multimedia has strong potential to be further developed through effectiveness testing to improve the numeracy skills of slow learners. This study implies the importance of developing contextual, interactive, and value-based learning media to support inclusive education.